Jumlah Anak Ideal di Provinsi Kalimantan Timur dan Faktor yang mempengaruhinya (Analisis Data SDKI 2017) - Sahvia Nandini; Ismail A.B; Rahmi Susanti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
East Kalimantan's total birth rate based on the 2017 IDHS is 2.7 less than the national target of 2.1, so the ideal number of children has not been achieved. The ordinal logistic regression analysis method can be used to help determine the factors that influence the ideal number of children. Objective : to determine the modeling of the factors that affect the ideal number of children in East Kalimantan Province used an ordinal logistic regression approach based on the 2017 IDHS data. Method : This was cross sectional. The independent variables include education, occupation, income, frequency of listening to radio, frequency of reading newspapers/magazines, frequency of watching television, internet use, knowledge of ovulation cycles and contraceptive use. The dependent variable was ideal number of children. The population was all women of childbearing age aged 15-49 years in East Kalimantan Province used the 2017 IDHS data totaling 1,221 people, with a sample of 902 people. Data analysis using ordinal logistic regression. Result : 60.2% of women had the ideal number of children. There is an effect of education (p value : 0.000), internet use (p value : 0.000) and contraceptive use (p value : 0.000) with the ideal number of children. There is no effect of occupation (p value : 0.067), type of income (p value : 0.674), frequency of listening to radio (p value), frequency of reading newspapers/magazines (p value : 0.378), frequency of watching television (p value : 0.428) , and knowledge of the ovulation cycle (p value: 0.182) with the ideal number of children. The magnitude of the influence of education (0.877), internet use (0.841) and contraceptive use (0.810) with the ideal number of children is strong. Testing the suitability of the model 0.984 > 0.05 means that the model is appropriate and the classification accuracy is 65% which means it is quite good. Conclusion : affect the ideal number of children in East Kalimantan Province include education, internet use and contraceptive use.